Manajemen Strategik di Era Disrupsi Digital dan Keberlanjutan: Studi Pustaka tentang Kepemimpinan, Teknologi, dan Transformasi Organisasi - Samodra Alfaridzi, Getar (Jurnal Manajemen dan Bisnis Kreatif, 2026)
Strategic management has undergone significant transformation in response to rapid digital disruption, technological advancement, and growing sustainability pressures. Organizations across sectors are increasingly required to integrate strategic leadership, digital capabilities, and sustainable governance in order to remain competitive and resilient in uncertain environments. This study aims to synthesize and critically examine contemporary scholarly perspectives on strategic management by focusing on the interrelationships among leadership, digital transformation, sustainability, and organizational change. Employing a qualitative research design based on a systematic literature review, this study analyzes peer-reviewed journal articles published in recent years that address strategic management challenges in diverse organizational and institutional contexts. The findings reveal that effective strategic management in the current era is strongly influenced by the alignment of leadership capabilities, technological readiness, and long-term sustainability orientation. Strategic leadership—characterized by ethical, relational, and inspirational dimensions—emerges as a key driver of successful strategic change and innovation. Moreover, digital technologies, including artificial intelligence and Industry 4.0 applications, play a pivotal role in reshaping strategic decision-making, organizational structures, and competitive dynamics. Sustainability considerations, such as environmental governance, ESG practices, and climate resilience, are increasingly embedded within strategic frameworks, transforming them from peripheral concerns into core strategic imperatives. This study contributes to the strategic management literature by offering an integrated conceptual understanding of how organizations navigate complexity and disruption through strategic alignment of leadership, technology, and sustainability. The findings also provide practical insights for managers and policymakers seeking to design adaptive and future-oriented strategic management approaches. Future research is encouraged to explore empirical validations of these integrated strategic frameworks across different industries and institutional settings.